Leukocyte profiles across the cardiovascular disease continuum: A population-based cohort study. (January 2020) - Groot, Hilde E.; van Blokland, Irene V.; Lipsic, Erik; Karper, Jacco C.; van der Harst, Pim
Abstract: Introduction: Inflammation plays a pivotal role across all stadia of the cardiovascular disease (CVD) continuum, i.e. non-obstructive coronary artery disease (CAD), myocardial infarction (MI), and ischemic heart failure (iHF). However, inflammation across CVD continuum has not been studied yet within one population. Therefore, we mapped leukocyte profiles across the continuum within the UK Biobank. Methods: The UK Biobank cohort study includes >500, 000 participants aged 40 to 70 years who were recruited from 22 assessment centers across the United Kingdom from 2006 to 2010. A total of 333, 218 individuals with available laboratory measurements at baseline were included in this study. These consisted of controls and individuals who had progression of CVD during follow-up (i.e. who developed CAD, MI, or iHF during follow-up). We investigated whether leukocytes and subtypes of leukocytes at baseline differed among the CVD continuum. Furthermore, we studied the possible interactions between sex and CVD on leukocytes. Results: Of 333, 218 individuals, 325, 054 (97.5%) individuals were categorized as controls, and 8164 (2.5%) individuals had progression of CVD during follow-up. Of those 8164 individuals, 4552 (1.4%) developed CAD during follow-up, 2839 (0.9%) MI, and 773 (0.2%) in iHF. Compared to controls, mean leukocyte levels at baseline increased across the CVD continuum from 6.8·10 9 cells/L (SD 1.7·10 9 cells/L) to 7.7·10 9 cells/L (SD 1.9·10 9 cells/L) ( P trend  = 2.19·10 −132 ) in individuals who developed iHF. This increase mainly depended on an increase in neutrophils. Furthermore, controls with leukocyte levels in the highest quartile at baseline had a 1.44 higher chance of being diagnosed with CAD during follow-up compared with individuals with leukocyte levels in lower quartiles (OR 1.44, 95% CI 1.34–1.56 P  = 9.63·10 −21 ). A similar increased change was observed for neutrophils, lymphocytes, monocytes, and eosinophils. There was a significant interaction between sex and CVD continuum on lymphocytes ( P  = 8.49·10 −5 ). Conclusion: Overall leukocyte count increased across the CVD continuum, which mainly depended on the increase in neutrophil count. High leukocytes in individuals not having CAD at baseline were predictive for the development of CAD during follow-up. Women had a greater increase of lymphocytes across the CVD continuum compared to men. Understanding which cells are key players in which stadium, could serve as a starting point for the identification of new potential therapeutic targets in CVD. Highlights: Overall leukocyte count increase across the cardiovascular disease (CVD) continuum. This increase mainly depends on the increase in neutrophil count. High leukocyte levels are predictive for the development of coronary artery disease. Women have a greater lymphocyte increase across the CVD continuum compared to men.